Seroprevalence of human immunodeficiency virus infection among whole blood donors at Sheri Kashmir Institute of Medical Sciences, Soura Srinagar - Rubiya Ryhan; Hilal Ahmad Tali; Falak Ara; Irshad Ahmad Tali; Kaneez Fatima; Shabir Ahmad Shiekh (Asian Journal of Medical Sciences, 2023)
Background: Blood transfusion has become a specialized modality of patient management and every year saves the millions of lives. However, it is not always safe and may lead to many life threatening complications among which transfusion-transmitted infections (TTIs) such as hepatitis and human immunodeficiency virus (HIV) are most significant and detrimental for the recipients. Hence, an integrated strategy for blood safety is required for the elimination of TTIs and or provision of safe and adequate blood transfusion services to the people. Aims and Objectives: To assess the seroprevalence of HIV infections among whole blood donors at Sheri Kashmir Institute of Medical Sciences (SKIMS), Soura, Srinagar. Materials and Methods: This was a hospital-based study carried in the postgraduate department of blood transfusion and immunohematology SKIMS, Soura, Srinagar over a period of 7 years from January 2015 to December 2021. All donor samples were screened for HIV by the ELISA method. Results: Overall, seroprevalence of HIV was found to be 0.013%. All the positive cases were male donors. Seroprevalence was the highest among replacement donors (0.011%) as compared to voluntary donors (0.001 %). Conclusion: It is very important to continue the screening of donated blood with highly sensitive and specific tests and to counsel donors who are reactive to any of the infectious diseases (like HIV, hepatitis B virus, HCV, syphilis, or malaria) and conduct extensive public awareness programs and measures to make transfusion of blood and blood components safe.